2015
DOI: 10.1007/s12149-015-0982-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of absolute Tc-99m tetrofosmin retention in the myocardium as an index of myocardial blood flow and coronary flow reserve by gated-SPECT/CT: a feasibility study

Abstract: Despite the low myocardial extraction fraction of Tc-99m tetrofosmin, an approximation of MBF and CFR is feasible with gated-SPECT/CT MPI. These flow indices together were able to discriminate CAD patients from controls and stratify different patient subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, since heart disease remains a major determinant of life expectancy, most general ICUs have integrated cardiology services. Patients presenting with an acute cardiac event are evaluated by utilizing bedside computerized tomography, which provides not only structural but also physiological/ functional data [23,24]. These data are exported into a nanotechnology interventional system that performs cardiac procedures when required (e.g.…”
Section: "Prediction Is Very Difficult Especially About the Future" mentioning
confidence: 99%
“…For example, since heart disease remains a major determinant of life expectancy, most general ICUs have integrated cardiology services. Patients presenting with an acute cardiac event are evaluated by utilizing bedside computerized tomography, which provides not only structural but also physiological/ functional data [23,24]. These data are exported into a nanotechnology interventional system that performs cardiac procedures when required (e.g.…”
Section: "Prediction Is Very Difficult Especially About the Future" mentioning
confidence: 99%
“…We did not examine normal healthy subject in this study, thus we could not confirm relevance of these risk factors and the MFR reduction. Earlier study showed the significant difference between the MFR of diabetic CAD patients and that of non-diabetics using a hybrid SPECT/CT camera (23). Moreover, they showed the association between age, sex, smoking habit, and reduced MBF.…”
Section: Discussionmentioning
confidence: 96%
“…In Apostolopoulos et al (2015), the MBF index was calculated for both rest and stress by combining 2-dimensional (2D) planar data with 3D SPECT. Immediately after tracer injection, the first-pass 2D planar images were acquired in early phases with high temporal resolution to obtain the integral of blood pool activity as input function.…”
Section: Dynamic Spect Of Mbf Using Conventional Rotational Spectmentioning
confidence: 99%